Wearable Antenna Mikrostrip Untuk Aplikasi Teknologi 5g - Pradiya, Rizan; Nugroho, Bambang Setia; Aziz, Arif Abdul (eProceedings of Engineering, 2024)
In daily life, there are still many challenges related to the long-range signal transmission, such as Wi-Fi and Bluetooth, which have a limited range of around 10 meters. To address this issue, we have developed a